2006
DOI: 10.5194/acp-6-1331-2006
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of NO, NO<sub>y</sub>, N<sub>2</sub>O, and O<sub>3</sub> during SPURT: implications for transport and chemistry in the lowermost stratosphere

Abstract: Abstract. We present measurements of NO, NO y , O 3 , and N 2 O within the lowermost stratosphere (LMS) over Europe obtained during the SPURT project. The measurements cover all seasons between November 2001 and July 2003. They span a broad band of latitudes from 30 • N to 75 • N and a potential temperature range from 290 to 380 K. The measurements represent a comprehensive data set of these tracers and reveal atmospheric transport processes that influence tracer distributions in the LMS. Median mixing ratios … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
128
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(138 citation statements)
references
References 50 publications
9
128
0
1
Order By: Relevance
“…Beside the interference with hydrocarbons in the sample air (see Sect. 2.2) or impurities in the added CO (Hegglin et al, 2006), this could have been induced by the pure air generator through a small contamination with any other N r compound. The overall calibration performance of a multi-month observation period is given in Fig.…”
Section: General Calibration and No 2 Conversionmentioning
confidence: 99%
“…Beside the interference with hydrocarbons in the sample air (see Sect. 2.2) or impurities in the added CO (Hegglin et al, 2006), this could have been induced by the pure air generator through a small contamination with any other N r compound. The overall calibration performance of a multi-month observation period is given in Fig.…”
Section: General Calibration and No 2 Conversionmentioning
confidence: 99%
“…Gas-phase CI instruments are more complex and are based on the reaction of ozone with either ethene or nitrogen oxide (Ridley et al, 1992;Hegglin et al, 2006;Williams et al, 2006;Bariteau et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…This mirrors the seasonal and latitudinal variation of the tropopause height, which enables the aircraft to reach deeper into the stratosphere at high latitudes in winter and spring when the tropopause is lowest. Additionally, strong diabatic descent from the overworld fills the lowermost stratosphere with O 3 -rich air during late winter/early spring (Hoor et al, 2004bHegglin et al, 2005). The model overestimates stratospheric O 3 mixing ratios at low latitudes during the spring and fall season (Figs.…”
Section: Seasonal and Latitudinal Variation Of O 3 Profilesmentioning
confidence: 98%
“…Details of the CO measurements can be found in Hoor et al (2004b). Ozone was measured independently by the FZJülich using UV absorption (time resolution 9 s, total uncertainty 5%) and the ETH Zürich via NO chemiluminescence (time resolution: 1 s; total uncertainty: 5%) (Hegglin, 2004;Hegglin et al, 2005). A linear regression analysis showed that both measurements agree within their uncertainty bounds (O 3 (CLD)=1.069 O 3 (UV)+5.4 (ppbv), R 2 =0.995; Hegglin, 2004).…”
Section: Observationsmentioning
confidence: 99%